COLLABORATIVE GOVERNANCE DALAM PENGELOLAN PARIWISATA DI KABUPATEN PROBOLINGGO - Firman Firdausi; Rifky Aldila Primasworo; Adil Abdillah (REFORMASI, 2023)
The meaning of governance is interpreted not only as a single player, namely the government. Along with the development of scientific governance, the paradigm of the Old Public Service, which positions the state as a single player, has been largely abandoned. One of the government affairs is the field of tourism. Tourism is one of the important commodities in the current era and for countries like Indonesia. Tourism is also one of the objects of development in Indonesia so that it becomes a strategic policy. Of course, these two things must be supported by actors from elements of governance other than the state, namely the private sector and the community. These elements are only properties, but from each of these elements there are still many actors who can play a role. Probolinggo Regency as one of the areas that has a lot of potential. It includes national, provincial and regional strategic areas. The focus of this research is the aspect of its management which turns out to have a fairly complex process in determining its roles and rights. As a result, each tourist destination has its own actors which can be divided depending on capital capability (for business entities) and authority (for state organs).AbstrakMakna governance dimaknai bukan hanya pemain tunggal yaitu pemerintah saja. Seriring dengan berjalannya perkembangan keilmuan pemerintahan paradigma Old Public Service yang memposisikan negara sebagai pemain tunggal sudah banyak ditinggalkan. Salah satu urusan pemerintahan adalah bidang pariwisata. Pariwisata menjadi salah satu komiditas penting di era sekarang dan bagi negara seperti Indonesia. Pariwisata juga menjadi salah satu obyek pembangunan di Indonesia sehingga menjadi kebijakan strategis. Kedua hal ini tentu harus ditopang aktor dari unsur governance selain negara yaitu swasta dan masyarakat.Â  Unsur ini hanya sifat, namun dari masing-masing unsur ini masih banyak aktor yang dapat berperan. Kabupaten probolinggo sebagai salah satu wilayah yang memiliki banyak potensi. Di dalamnya terdapat kawasan strategis nasional, provinsi, dan daerah. Fokus dari penelitian ini adalah aspek pengelolaannya yang ternyata terdapat proses yang cukup kompleks dalam penenutan peran dan haknya. Hasilnya setiap destinasi wisata memiliki aktornya masing-masing yang dapat dibagi tergantung kemampuan modal (untuk badan usaha) dan kewenangannya (untuk organ negara).